Spinal and bulbar muscular atrophy: the great imitator - Rinaldi, Carlo (Henry Stewart Talks, 2026)
Spinal and Bulbar Muscular Atrophy (SBMA), Molecular pathogenesis of SBMA, Potential therapeutic strategies, Diagnosis complexity, Overlapping symptoms, SBMA clinical trials, SBMA preclinical models